Ultra violet spectrophotometric method: Not possible for the simultaneous estimation of alpha one adrenoreceptor blockers (Journal of Pharmaceutical Negative Results, 2011)
Background: Although initially introduced for the management of hypertension, αladrenergic-receptor antagonists (α1 blockers) have become the standard of care for themedical management of benign prostatic hyperplasia (BPH)-related lower urinary tractsymptoms (LUTS). Alpha-blockers (alfuzosin, tamsulosin, doxazosin, prazosin, andterazosin) relax the smooth muscles in the prostate and are indicated for the symptomatictreatment of BPH, due to evidence of their positive and rapid effect on LUTS. Objective:Our objective was to develop and validate a method for simultaneous estimation ofthese drugs. Our aim was to develop a UV spectrophotometric method because ofthe simplicity and economical advantage of this technique. Materials and Methods:All these drugs were dissolved in the same solvent (methanol) and scanned under aShimadzuUV spectrophotomer, under full UV (ultraviolet) range (200 – 400 nm).Result:After some experiments we found that this is impossible. This was evident fromour study that UV spectra were overlapping each other, except in the case of tamsulosin.Conclusion: Same class of drugs may have almost the same functional groups, andgradient Reverse-Phase Liquid Chromatography(RPLC) will be more useful toseparate such complicated mixtures. Therefore, we propose to develop a gradient HighPerformance Liquid Chromatography(HPLC) method as it may be a more suitablemethod for the simultaneous estimation of these drugs.